2017
DOI: 10.1099/jmmcr.0.005077
|View full text |Cite
|
Sign up to set email alerts
|

Non-O1/non-O139 Vibrio cholerae septicaemia in a Saudi man: a case report

Abstract: Background. The non-O1/non-O139 serogroups of Vibrio cholerae occur in diverse natural niches, and usually cause mild and self-limiting gastrointestinal illness. However, they have well-documented potential to cause invasive and extra-intestinal infections among immunocompromised patients. Furthermore, their ability to grow in low-salinity surface water, and the existence of asymptomatic human carriers, suggest novel acquisition routes for this unusual infection, even in people without obvious risk factors.Cas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
15
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 40 publications
0
15
0
1
Order By: Relevance
“…Finally, although the lakes were not reservoir for epidemic V. cholerae the presence of V. cholerae non O1/non O139 that are known to cause localized outbreaks in some communities ( Bagchi et al, 1993 ) and diarrhea in travelers ( Bhattacharya et al, 1992 ) and other disease conditions such as septicemia, enteritis, bacteremia among other infections ( Chen et al, 2015 ; Deshayes et al, 2015 ; Kaki et al, 2017 ) is important for public health. Could it be that some of the localized outbreaks occurring in these communities are due to these pathogens?…”
Section: Discussionmentioning
confidence: 99%
“…Finally, although the lakes were not reservoir for epidemic V. cholerae the presence of V. cholerae non O1/non O139 that are known to cause localized outbreaks in some communities ( Bagchi et al, 1993 ) and diarrhea in travelers ( Bhattacharya et al, 1992 ) and other disease conditions such as septicemia, enteritis, bacteremia among other infections ( Chen et al, 2015 ; Deshayes et al, 2015 ; Kaki et al, 2017 ) is important for public health. Could it be that some of the localized outbreaks occurring in these communities are due to these pathogens?…”
Section: Discussionmentioning
confidence: 99%
“…5 NOVC causes gastroenteritis 6 and is related to extraintestinal infections, including skin and wound infections, otitis, bacteremia, biliary tract and urinary tract infections, pneumonia, peritonitis and meningitis. 4,7,8 Statistical analysis of 83 NOVC-infected patients in Taiwan from 2009-2014 showed that gastroenteritis was the most common illness due to NOVC (accounting for 54.2%), followed by biliary tract infection (14.5%) and primary bacteremia (13.3%). 9 Gastroenteritis can be mild to severe for both sporadic and break cases, but the prognosis of all cases is favorable.…”
Section: Discussion Epidemiologymentioning
confidence: 99%
“…Our review included 23 cases of NOVC bacteremia described in 18 reports from 2015-2019 (Table 2). [1][2][3][4][5]7,[10][11][12][13][14][15][16][17][18][19][20][21] The male-to-female ratio was 3.6:1, and the median age was 56 years. The youngest patient developed this disease at only 3 days of age, and the oldest patient was 83 years old.…”
Section: Discussion Epidemiologymentioning
confidence: 99%
“…Por lo anterior, la hipótesis que se propone, la cual no ha sido estudiada previamente, es que el factor de riesgo es el compromiso por obstrucción o infiltración de la vía biliar y no el tipo de tumor como tal. Esta hipótesis se apoya en el reporte de varios casos en los que se relacionó la infección con intervención de la vía biliar u obstrucción en pacientes sin factores de riesgo previamente descritos [6,11,12] ; sin embargo, esta debe ser evaluada en estudios analíticos para comprobar su relación.…”
Section: Discussionunclassified